2019
DOI: 10.1364/oe.27.001958
|View full text |Cite
|
Sign up to set email alerts
|

High-power two-cycle ultrafast source based on hybrid nonlinear compression

Abstract: We demonstrate a hybrid dual-stage nonlinear compression scheme, which allows the temporal compression of 330 fs-pulses down to 6.8 fs-pulses, with an overall transmission of 61%. This high transmission is obtained by using a first compression stage based on a gasfilled multipass cell, and a second stage based on a large-core gas-filled capillary. The source output is fully characterized in terms of spectral, temporal, spatial, and short-and long-term stability properties. The system's compactness, stability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 26 publications
(17 reference statements)
0
22
0
Order By: Relevance
“…Recently, multipass cells (MPC) either including a bulk medium [6] or filled with a rare gas [7][8][9] have been used to perform nonlinear temporal compression of femtosecond pulses in various regimes (normal dispersion [6][7][8][9], soliton compression in anomalous dispersion [10]), in a large range of pulses energies (from µJ [6,11] to mJ [7,9]), and output pulse durations (from >100 fs [6] to few cycles [10,12]). In all these demonstrations, it was observed that the MPC essentially acts like a 1D nonlinear object, with negligible impact of the nonlinearity on the spatial properties of the beams.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, multipass cells (MPC) either including a bulk medium [6] or filled with a rare gas [7][8][9] have been used to perform nonlinear temporal compression of femtosecond pulses in various regimes (normal dispersion [6][7][8][9], soliton compression in anomalous dispersion [10]), in a large range of pulses energies (from µJ [6,11] to mJ [7,9]), and output pulse durations (from >100 fs [6] to few cycles [10,12]). In all these demonstrations, it was observed that the MPC essentially acts like a 1D nonlinear object, with negligible impact of the nonlinearity on the spatial properties of the beams.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing efforts to improve the quality of this and other Yb-doped broadband gain materials are expected to bring further improvements to the achievable levels. In parallel to these efforts, large progress has been made in finding paths for efficient external pulse compression of these high-average power laser systems using hollow-core fibers [48], multi-pass cells [49][50][51][52], hybrid setups including multi-plate compressors [53], and even spectral broadening in the amplifier itself [54] bringing these applications one step closer. Additionally, as the pulse durations from these systems keeps getting shorter and approach the few-cycle regime, carrier-envelope phase control becomes increasingly relevant, in particular for high-power oscillators which can be used as powerful seeds for booster amplifiers [55,56].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the latest obtained results still remain moderate for the thin-disk geometry (13 W) [58], this represents an important first milestone in the potential direct generation of high-power few-cycle pulses at high average power. Furthermore, external pulse compression obviously allows for reaching few-fs pulse durations even starting from the (sub-) picosecond regime [51,52]. Finally, extending the wavelength coverage available from TDLs to longer wavelengths also represents a very promising research direction for ultrafast thin-disk oscillators and amplifiers, which would expand the application possibilities of these sources even further.…”
Section: Resultsmentioning
confidence: 99%
“…Shorter driving pulses allow exposure of the neutral gas atoms to higher laser intensities, or, alternatively, the use of heavier gases with larger n 2 , both resulting in larger nonlinear phase shifts  nl (t) ∝ n 2 I(t). To this end, substantial effort has been invested into the development of few-cycle laser amplifiers (13,14) and two-stage compression schemes (15)(16)(17), which mitigate the effects of ionization and plasma generation on the efficiency and compressibility of broad supercontinuum spectra.…”
Section: Introductionmentioning
confidence: 99%